(untitled) (Biological Sciences - PJSIR, 1998)
The chemistry of the novel hexadentate amino carboxylic acid ligand 1,4-diaminobenzene tetracetic acid is reported. The title compound (BDTA) can be compared with ethylene diamino tetracetic acid (EDTA) in its structural and characteristics on coordination to several metal ions. The complexes of (BDTA) with Cobalt (II), Nickel (II), Copper (II), Manganese (II) and Zinc (II) are prepared. The structural properties of the ligand and its complexes are proposed based on elemental analysis, UV-visible, Infra-red, NMR and thermogravimetric analysis and magnetic moments.